Pengaruh Konsentrasi PVA Terhadap Aktivitas Antioksidan Dan Sifat Fisik Masker Gel Peel Off Ekstrak Etanolik Daun Putri Malu (Mimosa pudica L) - Krisya, Otta Ganes; Januarti, Ika Buana; Susmayanti, Windi (Sultan Agung Islamic University of Semarang, 2023)
Background: The leaves of Putri malu (Mimosa pudica L.) contain flavonoid compounds which act as antioxidants to prevent and reduce the effects of free radicals on the skin. The potency of this ingredient is formulated into a peel-off mask with a PVA gel base because it can help penetrate the active substance into the skin by forming a strong and plastic film that provides good contact between the drug and the skin. The purpose of this study was to determine the effect of PVA concentration on the physical properties and antioxidant activity of the Mimosa Pudica L. ethanolic extract peel-off gel mask. Methods: The leaves of Putri malu were extracted by maceration using 70% ethanol and then peel-off mask preparations were made with PVA concentrations of 8%, 10% and 12%. The masks were tested for physical properties including organoleptic tests, pH strength tests, viscosity and dry time tests as well as antioxidant activity. The data obtained was then analyzed using One Way ANOVA and Kruskall Wallis. Results: EEDPM Peel-Off Mask formula 1 produced an IC50 of 5.505 μg/ml, formula 2 1.088 μg/ml and formula 3 0.606 μg/ml which means that the three formulas have strong antioxidant activity. Conclusion: The higher the concentration of PVA in the ekstrak etanolik daun putri malu (EEDPM) peel-off gel mask, the stronger the antioxidant activity.